Condensation of (E)-5-Aryl-3-Arylmethylene-2-(3H)- Furanones with Different Amines - M. Abdallah, Shadia; A. Saad, Hanna; A. Hefny, Halima; H. Yehia, Hadia; H. Abdou, Mervat (Asian Journal of Chemistry, 2010)
Condensation of (E)-2(3H)-furanones (1-8) with different amines gives the corresponding (E)-N-substituted-3-aroyl-2-arylmethylene propionamides and 5-substituted amino-5-aryl-3-arylmethylene butyrolactones (9-36). The structures of compounds obtained were assigned in accordance with their elemental analysis, 1H NMR, MS and FTIR.